Smart farming - Gitlin, Marty (21st century skills innovation library. Exploring the internet of things., 2021)
Investigates the history, creation, and operation of smart farming technology. Highlights robotic harvesting machines, devices to track the health of farm animals, and tractors that can drive themselves by GPS. Includes a glossary.